Decreased Peripheral Blood Lymphocyte Count Predicts Poor Treatment Response in Peritoneal Dialysis-Associated Peritonitis - He Y; Huang X; Zhang J; Liao J; Huang H; He Y; Gao M; Liao Y; Xiong Z (Dove Medical Press, 2023)
YuJian He,1,2 XiaoYan Huang,1 Jingwen Zhang,1 Jinlan Liao,1 Huie Huang,1 Yan He,1 Min Gao,1 Yumei Liao,1 Zibo Xiong1 1Renal Division, Peking University Shenzhen Hospital, Shenzhen, People's Republic of China; 2Renal Division, PKU-Shenzhen Clinical Institute of Shantou University Medical College, Shenzhen, People's Republic of ChinaCorrespondence: Zibo Xiong, Renal Division, Peking University Shenzhen Hospital, Shenzhen, People's Republic of China, Tel +86-13510880599, Fax +86-755-83089011, Email xiong0301@163.comPurpose: Peripheral blood lymphocyte counts is a pivotal parameter in assessing the host's immune response during maladies and the equilibrium of the immune system which has been found to correlate with various diseases progression and prognosis. However, there was no study on patients with peritoneal dialysis-associated peritonitis (PDAP). We sought to investigate the prognostic value of baseline peripheral blood lymphocyte count in PDAP patients.Patients and methods: This retrospective study analyzed data from 286 PDAP patients over nine years. Episodes were categorized according to the tertiles of peripheral blood lymphocyte counts (Very Low Lymphocyte Count (VLLC) Group, < 0.72× 106/L; Low Lymphocyte Count (LLC) Group, 0.72- 1.11× 106/L; Normal Lymphocyte Count (NLC) Group, ≥ 1.11× 106/L). Demographic, laboratory, and infection-related variables were analyzed. Cox regression and generalized estimating equation (GEE) models were used to estimate the association between lymphocyte counts and PDAP treatment failure, which included PD catheter removal and death.Results: After adjusting for other potential predictors, decreased lymphocyte counts exhibited an incremental relationship with the risk of treatment failure. The VLLC group indicated a 270% (95% CI, 1.168- 6.247, P=0.020) and 273% (95% CI, 1.028- 7.269, P=0.044) increased venture of treatment failure in Cox regression and GEE analyses, respectively, compared with the NLC group. As a continuous variable, the restricted cubic spline showed a linear negative correlation between lymphocyte counts and the treatment failure risk (P for overall = 0.026). The multivariate model C (combined lymphocyte count with baseline age, sex, dialysis age, Charlson Comorbidity index (CCI), etiology of kidney failure, hemoglobin, albumin, total bilirubin and infection type) showed an area under the curve of 0.824 (95% CI, 0.767- 0.881, P=0.001) for the prediction of treatment failure.Conclusion: Lower lymphocyte counts are linked to increased PDAP treatment failure risk. This highlights lymphocyte count's potential as a prognostic indicator for PDAP.Keywords: peritoneal dialysis-associated peritonitis, lymphocyte counts, prognosis, treatment failure